2022
DOI: 10.1002/smll.202108034
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Steam Induced Surface Oxygen Vacancy onto Ni–Fe Bimetallic Nanocomposite for CO2 Electroreduction

Abstract: Surface oxygen vacancies (Vo) regulation is an effective strategy to improve the electrochemical CO2 reduction reaction (CO2RR) performance by lowering the activation energy barrier of CO2; however, the lack of precise control over the local atomic structures severely hinders the large‐scale application of Vo‐activated electrocatalyst for CO2RR. Herein, an efficient strategy to facilitate CO2 activation is developed by introducing Vo into transition metal nanoparticles (NPs) with a steam‐assisted chemical vapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…S5, Table S1, ESI †). [39][40][41] This change also affects the electronic structure of oxygen atoms: the H-60 shows the strongest O 1s peak possibly adjacent to the W 5+ at 531.4 eV (Fig. 2j).…”
Section: Resultsmentioning
confidence: 99%
“…S5, Table S1, ESI †). [39][40][41] This change also affects the electronic structure of oxygen atoms: the H-60 shows the strongest O 1s peak possibly adjacent to the W 5+ at 531.4 eV (Fig. 2j).…”
Section: Resultsmentioning
confidence: 99%
“…DFT calculations confirmed that H-NiFe/NG featured the lowest energy barrier for the formation of the COOH* intermediate, thus exhibiting a superior catalytic performance for the CO 2 RR. 249 Liu et al reported the synthesis of an Fe-Cu DMC for electrochemical CO 2 RR via the thermal pyrolysis of Fe-and Cu-doped ZIF-8. The Fe-Cu dual sites were confirmed by aberration-corrected HAADF-STEM given that many distinct dual dots were observed on the substrate.…”
Section: Co 2 Rrmentioning
confidence: 99%
“…based on their atomic orbitals further proved that more active carriers exist in the lateral orbital of Co-CH@Ni-MOFs composite, which may enhance the adsorb ability and electrochemical reactivity. [44][45][46] For the molecular dynamic (MD) simulations, fluctuating curves of energy and temperature (Figure 5) obtained after adsorbing OH − on as-prepared materials revealed that a reasonable equilibrium state was reached in the 500 ps simulation. The adsorption behaviors with adsorption energy of OH − on the Co-CH, Ni-MOFs, and Co-CH@Ni-MOFs materials (Figure 6) clearly show that the heterostructure of Co-CH@Ni-MOFs increases the adsorption property for OH − ions on the interface with adsorption energy of −1.51 kcal mol −1 , higher than −0.88 kcal mol −1 of Co-CH and −1.00 kcal mol −1 of Ni-MOFs.…”
Section: Characterization Of Co-ch Ni-mofs and Co-ch@ni-mofsmentioning
confidence: 99%